2016
DOI: 10.1111/apa.13454
|View full text |Cite
|
Sign up to set email alerts
|

Hand‐held computers can help to distract children undergoing painful venipuncture procedures

Abstract: Playing a game on a hand-held computer meant that only one in six children reported pain during venipuncture, but it was not superior to being distracted by nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
(37 reference statements)
1
23
0
1
Order By: Relevance
“…However, an Italian study with 200 children between the ages of 4 and 13 years undergoing venipuncture found no differences in outcomes for a headheld computer game named Angry Birds compared with a nurse-lead low-tech distraction. Using self-report indicators of pain, both high-tech and low-tech distraction interventions were effective in about 85% of children (Franca et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, an Italian study with 200 children between the ages of 4 and 13 years undergoing venipuncture found no differences in outcomes for a headheld computer game named Angry Birds compared with a nurse-lead low-tech distraction. Using self-report indicators of pain, both high-tech and low-tech distraction interventions were effective in about 85% of children (Franca et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This randomised controlled trial by Franca Crevatin et al compared the efficacy of children playing the Angry Bird game on a hand‐held computer with nurse‐led distraction in a blood drawing centre in Italy. Only one in six children in the computer game group reported pain during venipuncture, which was as effective as being distracted by nurses .…”
Section: Hand‐held Computers Can Help To Distract Children During Paimentioning
confidence: 95%
“…One RCT assessing use of restraint during venepuncture showed a decreased need for restraint 41 when a child used an interactive video game compared with standard care. Evidence from the included studies did not suggest a significant effect of interactive games on the following outcomes: anaesthetic induction time (n¼1 RCT), 42 length of surgery (n¼1/1 RCT), 43 postoperative length of stay (n¼2/2 RCTs), 42,43 postoperative behavioural change (n¼3/3 RCTs), 26,44,45 analgesia usage (n¼3/3 RCTs), 43,46,47 time taken for venepuncture (n¼3/3 RCTs), 41,48,49 number of venepuncture attempts/first venepuncture success rate (n¼3/3 RCTs), 41,50,51 or need for sedation during venepuncture (n¼1/1 RCT). 41 There was mixed evidence on whether the use of interactive video games was associated with children's improved burns wound healing (n¼1/2 RCTs found an improvement; the other found no difference between groups), 46,52 perioperative procedural compliance (n¼2/3 RCTs found an improvement; the other found no difference between groups), 45,53,54 anaesthetic emergence delirium (n¼2/3 RCTs found no difference between groups; the other found interactive video games improved emergence delirium), 43,47,53 or length of burns treatment procedure (n¼4/6 RCTs found no difference between groups; the other two found reduced time of treatment procedure).…”
Section: Other Medical Outcomesmentioning
confidence: 99%
“…46,52,55e58 Adverse events of using interactive video games Studies that examined adverse events most commonly included nausea, vomiting, or motion sickness within their definition of adverse events (n¼9/10 RCTs), 41,48,49,54,56,58e61 with the remaining RCT not providing a definition. 51 Dizziness, headache, seizures, and claustrophobia were other less commonly monitored outcomes which were also included (n¼3/9 RCTs). 41,49,54 Most studies reported that zero adverse events occurred (n¼6/10 RCTs).…”
Section: Other Medical Outcomesmentioning
confidence: 99%